Sinonasal small-cell carcinoma combined concurrently with small-cell lung carcinoma: case report and literature review - Quan, Rencui; Han, Ling; Wu, Shihai; Li, Xianming (Frontiers in Immunology, 2025)
Sinonasal small-cell neuroendocrine carcinoma (SCNEC) is an uncommon malignant epithelial neuroendocrine tumor in the sinonasal cavity that often presents in isolation and rarely occurs in synchronous fashion with small-cell lung carcinoma (SCLC). Here, we present a case of a 65-year-old man diagnosed with SCNEC concurrently combined with SCLC. He received first-line platinum-doublet chemotherapy combined with durvalumab, followed by radiotherapy to thoracic as well as head and neck regions. The follow-up computed tomography and magnetic resonance imaging showed a complete response according to Response Evaluation Criteria in Solid Tumors criteria until 9 June 2024. This case highlights the need for accurate diagnostic characterization of primary lesions and the need to formalize treatment paradigms using chemotherapy, radiation therapy, immunotherapy with immune checkpoint inhibitors, and targeted prophylactic cranial irradiation.